2001
DOI: 10.1071/ar01035
|View full text |Cite
|
Sign up to set email alerts
|

A single gene controls resistance to septoria nodorum blotch in the Aegilops tauschii accession AUS21712

Abstract: A potential source of resistance to septoria nodorum blotch had been identified in an accession of the wild wheat, Aegilops tauschii. A cross was made between the resistant Ae. tauschii accession, AUS21712, and a susceptible accession, CPI110889, to study the genetics of resistance. The parental accessions and the F1, F3, and F4 progeny were screened in the glasshouse as seedlings. The resistant parent took significantly longer to develop symptoms, developed significantly fewer lesions, and expressed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Additionally, the classical gene-for-gene interaction and the S. nodorum-wheat interaction differs in that the toxins tend to act additively as virulence factors rather than in an epistatic fashion, therefore host lines sensitive to multiple toxins often have increased susceptibility over lines with single toxin sensitivities (Friesen et al, 2007). This fact provides a valid explanation for the numerous relatively minor QTLs with predominantly additive effects identified in several populations (reviewed by Xu et al, 2004) as well as the studies identifying single major genes accounting for resistance/ susceptibility (Kleijer et al, 1977;Ma & Hughes, 1995;Murphy et al, 2000). For example, if a single toxin sensitivity is segregating in a population, only one major locus conferring resistance would be identified.…”
Section: Stagonospora Nodorum Host-selective Toxinsmentioning
confidence: 94%
“…Additionally, the classical gene-for-gene interaction and the S. nodorum-wheat interaction differs in that the toxins tend to act additively as virulence factors rather than in an epistatic fashion, therefore host lines sensitive to multiple toxins often have increased susceptibility over lines with single toxin sensitivities (Friesen et al, 2007). This fact provides a valid explanation for the numerous relatively minor QTLs with predominantly additive effects identified in several populations (reviewed by Xu et al, 2004) as well as the studies identifying single major genes accounting for resistance/ susceptibility (Kleijer et al, 1977;Ma & Hughes, 1995;Murphy et al, 2000). For example, if a single toxin sensitivity is segregating in a population, only one major locus conferring resistance would be identified.…”
Section: Stagonospora Nodorum Host-selective Toxinsmentioning
confidence: 94%
“…The genetic study indicated that resistance to SNB in six hexaploid wheat genotypes was controlled by the same recessive gene. Single‐gene resistance to SNB has been reported from only three studies, all of which were conducted at the seedling stage under controlled environmental conditions (Frecha, 1973; Ma and Hughes, 1995; Murphy et al, 2000). Comparison of these and our study, with those studies reporting resistance to be polygenically controlled, suggested several factors that could explain the different results.…”
Section: Discussionmentioning
confidence: 99%
“…These include a dominant gene on chromosome 1B in winter wheat cultivar Atlas 66 (Kleijer et al, 1977) and a dominant gene in an Aegilops tauschii Coss. (DD) accession (Murphy et al, 2000). In addition to these genes, polygenes, which function together to control a quantitatively expressed resistance, have been located on several chromosomes in the A, B, and D genomes (Nicholson et al, 1993; Hu et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have shown that resistance to the leaf and head phases may be under separate genetic control (Bostwick et al , 1993; Hu et al , 1996; Wicki et al , 1999). Several independent genes that regulate glume and flag leaf resistance have been identified (Fried and Meister, 1987; Aguilar et al , 2005), although single genes have been identified in some Triticum accessions (Parlevliet, 1977; Ma and Hughes, 1995; Murphy et al , 2000; Feng et al , 2004). Disease resistance is often highly correlated with late-maturing, tall cultivars (Scott, 1973; Eyal, 1981; Trottet and Merrien, 1982; Aguilar et al , 2005).…”
Section: Introductionmentioning
confidence: 99%